Problem with pulse action for a linear stochastic parabolic equation of higher order - Perun, H. M.; Перун, Г. М. (Institute of Mathematics, NAS of Ukraine, 2008)
We prove a theorem on the well-posedness of the Cauchy problem for a linear higher-order stochastic equation of parabolic type with time-dependent coefficients and continuous perturbations whose solutions are subjected to pulse action at fixed times.